A Strategic Engagement Model for Electoral Participation: Insights from Indonesia’s Local Election Governance - TALIA, Nita Talia (PT Keberlanjutan Strategis Indonesia, 2025)
Declining voter participation has emerged as a global democratic concern, reflecting a growing gap between institutional governance and citizen engagement. In emerging democracies, particularly within decentralized systems, electoral institutions often struggle to sustain meaningful participation beyond procedural compliance. This study addresses that gap by developing a Strategic Engagement Model that integrates institutional strategy, collaborative networks, and citizen trust to enhance electoral participation. Using a qualitative descriptive approach, the research draws on empirical evidence from the Komisi Pemilihan Umum (KPU) Lamongan in East Java, Indonesia, through in-depth interviews, direct observations, and document analysis. Findings reveal that Lamongan’s voter turnout increased from 78.53% in 2019 to 81.95% in 2024, surpassing the national target. This improvement was driven by adaptive institutional planning, multi-stakeholder collaboration, and inclusive communication strategies that bridged bureaucratic mechanisms with community participation. Theoretically, the study contributes to the literature on strategic governance and institutional trust by conceptualizing engagement as a cyclical, co-productive, and value-driven process rather than a linear administrative function. Practically, it demonstrates how local electoral bodies can operationalize democratic resilience through flexible, participatory, and context-sensitive governance mechanisms. By situating the Lamongan experience within Indonesia’s broader democratic framework, this study offers both an analytical model and policy insights for enhancing legitimacy and sustainability in local electoral governance. The findings underscore that strengthening democracy requires adaptive institutions and citizen-centered engagement.